Leadership factors of educational leaders, organizational culture and teacher competence in Selected Private Higher Education Institutions (HEIS) in Binan, Laguna - Abustan, Arcangel Joshua; Ali, Aina; Bautista, Susana; Bermudo, Pedrito Jose; Serrano, Ernesto, Jr.; Yango, Antonio (Technium Social Sciences Journal, 2023)
The study aimed to identify the relationship between leadership factors, organizational culture and teacher competence in private higher education institutions. Descriptive correlational research design was used in this study. The study revealed that leadership factors of the educational leaders was highly favorable with an average weighted mean of 3.39, the organizational culture was highly favorable with an average weighted mean of 3.37, the teacher competence was very high with an average weighted mean of 3.38. Correlations indicated that there was a significant relationship between Leadership Factors and Organizational Culture, Leadership Factors and Teacher Competence as well as Organizational Culture and Teacher Competence. The results also showed that there was a high level of prediction of the dependent variable (level of Teacher Competence). The obtained R square of 0.823 shows that independent variables (leadership factors and organizational culture) explain the variability of the dependent variable (level of teacher competence). Further, the independent variables leadership factors along attitude, determination and motivation and organizational culture in terms of create, collaborate and control are the drivers of teacher competence in higher education institutions.